Morphological characters of the endemic honey bee Apis binghami binghami across different elevations in South Sulawesi, Indonesia - JAENAR ADELIA NADI; SITTI NURAENI; BUDIAMAN BUDIAMAN; ANDI PRASTIYO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nadi JA, Nuraeni S, Budiaman, Prastiyo A. 2026. Morphological characters of the endemic honey bee Apis binghami binghami across different elevations in South Sulawesi, Indonesia. Biodiversitas 27 (2): d270220. https://doi.org/10.13057/biodiv/d270220. Apis binghami binghami is an endemic honey bee of Wallacea that plays a crucial role in pollination and maintaining tropical ecosystem balance. However, information on its morphological characters along the elevational gradient in South Sulawesi remains limited. Environmental heterogeneity associated with altitude may strongly influence morphological traits related to flight performance, foraging efficiency, and physiological adaptation. This study aimed to analyze the morphological characters of A. b. binghami across three elevational zones lowland (0-300 masl), midland (301-700 masl), and highland (>700 masl) in South Sulawesi, Indonesia. Worker bees were collected using standardized bait traps, with 30 individuals sampled from each elevation. A total of 37 morphometric characters were measured using stereo microscopy. Data were analyzed using one-way Analysis of Variance (ANOVA), Principal Component Analysis (PCA), cluster analysis, and correlation analysis. The results revealed significant morphometric differences (p<0.001) among elevations, with increasing body size, wing length, abdomen, and sting dimensions at higher altitudes. PCA showed that the first principal component explained 80.22% of the total variation, primarily influenced by mesoscutum width, forewing length, including tegula, and abdominal length. Cluster analysis separated highland populations from lowland and midland groups, indicating clear morphological differentiation along the elevational gradient. These findings demonstrate pronounced morphological plasticity of A. b. binghami in response to altitude-related environmental conditions. The study provides the first comprehensive morphometric dataset for this endemic subspecies in South Sulawesi and offers important insights for conservation planning.